Acquired modification of sphingosine-1-phosphate lyase activity is not related to adrenal insufficiency - BEREKET, ABDULLAH; GÜNAL, DİLEK; HAKLAR, GONCAGÜL; SÜNTER, GÜLİN; AĞAN YILDIRIM, KADRİYE; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (BIOMED CENTRAL LTD, 2018)
Background: Congenital sphingosine-1-phosphate (S1P) lyase deficiency due to biallelic mutations in SGPL1 gene has recently been described in association with primary adrenal insufficiency and steroid-resistant nephrotic syndrome. S1P lyase, on the other hand, is therapeutically inhibited by fingolimod which is an oral drug for relapsing multiple sclerosis (MS). Effects of this treatment on adrenal function has not yet been evaluated. We aimed to test adrenal function of MS patients receiving long-term fingolimod treatment. Methods: Nineteen patients (14 women) with MS receiving oral fingolimod (Gilenya (R), Novartis) therapy were included. Median age was 34.2 years (range; 21.3-44.6 years). Median duration of fingolimod treatment was 32 months (range; 6-52 months) at a dose of 0.5 mg/day. Basal and ACTH-stimulated adrenal steroid measurements were evaluated simultaneously employing LC-MS/MS based steroid panel. Basal steroid concentrations were also compared to that of sex- and age-matched healthy subjects. Cortisol and 11-deoxycortisol, 11-deoxycorticosterone and dehydroepiandrosterone were used to assess glucocorticoid, mineralocorticoid and sex steroid producing pathways, respectively. Results: Basal ACTH concentrations of the patients were 20.8 pg/mL (6.8-37.8 pg/mL) (normal range; 5-65 pg/mL). There was no significant difference in the basal concentrations of cortisol, 11-deoxycortisol, 11-deoxycorticosterone and dehydroepiandrosterone between patients and controls (p = 0.11, 0.058, 0.74, 0.15; respectively). All patients showed adequate cortisol response to 250 mcg IV ACTH stimulation (243 ng/mL, range; 197-362 ng/mL). There was no significant correlation between duration of fingolimod treatment and basal or ACTH-stimulated cortisol or change in cortisol concentrations during ACTH stimulation test (p = 0.57, 0.66 and 0.21, respectively). Conclusion: Modification and inhibition of S1P lyase activity by the long-term therapeutic use of fingolimod is not associated with adrenal insufficiency in adult patients with MS. This suggests that S1P lyase has potentially a critical role on adrenal development rather than the function of a fully mature adrenal gland.
Keywords: Sphingosine-1-phosphate lyase; Fingolimod; Adrenal; Multiple sclerosis; MULTIPLE-SCLEROSIS; NEPHROTIC SYNDROME; FINGOLIMOD; MUTATIONS; CELLS